VD_FINDINFO Arrêt / 2024 / 76 vom 5. Februar 2024 - VD Tribunal cantonal (2024)
DEGRÉ DE L'INVALIDITÉ, ÉVALUATION DE L'INVALIDITÉ, APPRÉCIATION DES PREUVES | 28 al. 1 LAI, 4 LAI, 16 LPGA, 61 let. c LPGA, 8 LPGA